Writing an effective and supportive recommendation letter. (5th March 2021) - Sarabipour, Sarvenaz; Hainer, Sarah J.; Furlong, Emily; Jadavji, Nafisa M.; de Winde, Charlotte M.; Bielczyk, Natalia; Shah, Aparna P.
Abstract : Writing recommendation letters on behalf of students and other early‐career researchers is an important mentoring task within academia. An effective recommendation letter describes key candidate qualities such as academic achievements, extracurricular activities, outstanding personality traits, participation in and dedication to a particular discipline, and the mentor's confidence in the candidate's abilities. In this Words of Advice, we provide guidance to researchers on composing constructive and supportive recommendation letters, including tips for structuring and providing specific and effective examples, while maintaining a balance in language and avoiding potential biases. Abstract : How can researchers write a supportive recommendation letter for a mentee or a colleague? What considerations must be made to write appropriate letters for different opportunities? This Words of Advice article provides guidance to researchers on composing effective recommendation letters, including tips for structuring and supporting the letter with relevant specific information, while maintaining a balance in language and avoiding potential biases.